Peran Kepemimpinan Transformasional Kepala Sekolah dalam Pengelolaan SDM: Kajian Pustaka terhadap Dampaknya pada Kinerja Guru - Ahmad Ridani; Sudadi Sudadi (BISMA : Business and Management Journal, 2025)
This study aims to examine the role of transformational leadership of school principals in human resource management (HR) and its impact on teacher performance through a literature review approach. Transformational leadership is understood as a leadership style that is able to inspire, motivate, and transform individuals to reach their maximum potential. This study uses literature study methods from various scientific sources, both national and international journals, which are relevant to the themes of educational leadership, human resource management, and teacher performance. The results of the study show that school principals with a transformational leadership style have a significant influence on school human resource management, especially in terms of professional development, increased work motivation, and the formation of a positive organizational culture. The impact of these leadership practices is consistently associated with increasing teacher performance in pedagogic aspects, professional competence, and loyalty to the institution. This study recommends strengthening the capacity of transformational leadership in school principals through leadership training and ongoing professional development programs.